Changes in Chinese Discharged Chronic Mental Patients Attending a Psychiatric Rehabilitation Program with Holistic Care Elements: A Quasi-Experimental Study - Andrew L. Luk; Daniel T.L. Shek (The Scientific World Journal)
This study attempted to examine the changes and related factors in discharged chronic mental patients attending a psychiatric rehabilitation program in Hong Kong adopting a self-help group (SHG) approach with holistic care emphases on the physical, psychological, social, and spiritual functioning of the program participants. A quasi-experimental design involving an experimental group (109 participants attending the program) and a control group (154 patients from a psychiatric outpatient clinic who had never attended any SHG before) was adopted with the participants responding to measures assessing their functioning in the physical, psychological, social, and spiritual domains. Results showed that those who joined the SHG with holistic care elements had more friends and more social satisfaction than the control subjects. Duration of attendance, religious involvement, and group involvement were three key factors related to the outcomes of the program participants. This pioneering study provides support for the effective use of the SHG approach with holistic care elements to help discharged chronic mental patients in the Chinese culture.